FEMINISME DALAM PERSPEKTIF ISLAM DAN BARAT (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2022)
This study aimed at investigating Arthur Schopenhauer and Murtadha Muthahhari's perspectives on feminisme. This study employed a qualitative approach. This is a library research in which data were collected from related literatures. Descriptive analytical and historical analytical methods were used to analyze data. The findings of the study showed that perspectives on feminisme between both scholars are different. Arthur Schopenhauer views that feminisme is debatable. Meanwhile, Murtadha Muthahhari emphasized that feminism it is not necessary to debate it because it has been clearly stated in the Holy Quran. This research recommends educational institutions and other social institutions to view feminisme as a path to woman's equality. Keywords: Comparison; Feminism; Perspective.